Molecular Impact of the Tumor Microenvironment on Multiple Myeloma Dissemination and Extramedullary Disease - Forster, Stefan; Radpour, Ramin (Frontiers in Oncology, 2022)
Multiple myeloma (MM) is the most common malignant monoclonal disease of plasma cells. Aside from classical chemotherapy and glucocorticoids, proteasome inhibitors, immunomodulatory agents and monoclonal antibodies are used in the current treatment scheme of MM. The tumor microenvironment (TME) plays a fundamental role in the development and progression of numerous solid and non-solid cancer entities. In MM, the survival and expansion of malignant plasma cell clones heavily depends on various direct and indirect signaling pathways provided by the surrounding bone marrow (BM) niche. In a number of MM patients, single plasma cell clones lose their BM dependency and are capable to engraft at distant body sites or organs. The resulting condition is defined as an extramedullary myeloma (EMM). EMMs are highly aggressive disease stages linked to a dismal prognosis. Emerging literature demonstrates that the dynamic interactions between the TME and malignant plasma cells affect myeloma dissemination. In this review, we aim to summarize how the cellular and non-cellular BM compartments can promote plasma cells to exit their BM niche and metastasize to distant intra-or extramedullary locations. In addition, we list selected therapy concepts that directly target the TME with the potential to prevent myeloma spread.